Analysis of the hydraulic impacts of the Lakeshore Expressway-Dike on Laguna Lake using numerical simulation - Dela Cruz, Raymond T.
More than twenty typhoons hit the Philippines every year. For the past years, the intensity of the rain brought by these typhoons have caused perennial flooding in Metro Manila, more specifically the coastal areas of Laguna Lake. To mitigate this problem the Department of Public Works and Highways (DPWH) in coordination with Laguna Lake Development Authority (LLDA) approved and started the implementation of the Laguna Lakeshore Expressway - Dike Project (LLEDP). This is a 47 km long expressway - dike that will run from Taguig to Los Banos along the western coast of the lake to protect the shore land areas from flooding. This study focused on the impacts of the LLEDP on the lake hydraulics using numerical simulation. This was done by setting up a hydrodynamic model of the lake system and analysis on the impacts of the project. This is accomplished by using a multidimensional hydrodynamic modelling software, Delft3D, to set up the Laguna Lake model. The model was calibrated using Manning's roughness coefficient of 0.02 for Laguna lake and 0.06 for the Pasig River with a root - mean - square error (RMSE) of 9.08%. This was validated using water level with a RMSE of 8.78% and velocity circulation. The validated model was then used as baseline condition in assessing a with and without project scenario using hydraulic parameters of the lake. The parameters analyzed were flow circulation, depth averaged velocity, bed shear stress and the water level. Results of the simulation showed that the flow circulation patterns did not vary much between the baseline and dike scenario for both the wet and dry conditions. During the wet season, the current pattern moves towards the Napindan Channel with the water going out of the lake. However, during the dry season the flow is reversed, the water flows into the lake. Moreover, the changes in the water level and cumulative discharge did not vary much as well. A mean discharge rate of 235.4 cu. m/s and back flow rate of 137.9 cu. m/s was simulated in the baseline scenario and mean discharge rate and back flow rate of 232.9 cu. m/s and 143 cu. m/s respectively, for the dike scenario. After comparing the base line scenario and the dike scenario for the depth averaged velocity and bed shear stress, it was found out that during the wet season, areas of high water current found near the mouth of Napindan channel to the South Bay are also areas of high bed shear stress. These areas are expected to be erosion - prone areas considering high magnitudes of velocity and bed shear stress. Furthermore, high magnitude of high shear stress promotes sediment transport, thus occurrence of such is at high probability. During the dry season, the impacts differed. A decrease in the magnitude was observed in the East, South and West bays of the lake for both the velocity and shear stress. However, an increase occurred in the Central bay. It is therefore concluded that the lakeshore expressway - dike is expected to affect the hydrodynamics of the lake and should be properly incorporated in designs and lake management decision - making. Recommendations to further improve this study includes incorporating wave dynamics, dike slope configuration effects and performing a 3-D simulation on the project.